SPECIAL ARTICLE COVID-19: Ear, Nose, and Throat Practice Guidelines: An Update for COVID-19 - Kapoor,Sahil (2021)
Abstract Introduction Amidst another wave of COVID-19, the alarming number of cases per day in India has affected the healthcare system and professionals tremendously. As the disease burden continues to increase, ear, nose, and throat (ENT) specialists remain at high risk of exposure to this aerosol borne virus. This requires the creation and regulation of protocols for conducting routine clinical practice, especially by ENT specialists. Objectives To review the available literature and to propose strategies and recommendations for ENT practitioners to conduct their regular practice amidst this pandemic. Data synthesis A systematic review of the available literature on ENT practice during the COVID-19 pandemic was done. Out of the many protocols proposed in various studies, the most practical and feasible ones that could be adopted by practicing ENT doctors/ surgeons in the long run were selected. Adequate precautions and use of high level of personal protective equipment (PPE) is required to be adopted by all practicing ENT doctors. Use of teleconsultation has been promoted as it limits face-to-face exposure. Proper guidelines should be followed for both emergency and elective surgeries. Endoscopy can be used as a safe and useful tool for ENT examination. Conclusion As practicing otorhinolaryngologists, it is of utmost importance that we take all necessary precautions and adopt safety measures in our clinical practice while conducting out patient department (OPD) consultations, operative procedures, and emergency care to protect our patients, ourselves, and other healthcare staff during this time.